Dynamique d'infestation de la forêt classée de Sanaimbo par les adventices à partir des agro-écosystèmes environnants - Touré, A.; Adou, LMD.; Kouamé, KF.; Ipou Ipou, J. (Tropicultura, 2016)
Dynamics of Infestation in the Sanaimbo Protected Forest by Weeds from Surrounding Agro-ecosystems. The infestation dynamics of the Sanaimbo Protected Forest by weeds was evaluated with the aim to quantify the impact of weeds on the original flora of this locality. Floristic and phytosociological surveys samples were carried out on plots located inside and outside the forest. The frequency and proportion of biological types is different in plots located outside and within the classified forest. Chromolaena odorata (L.) King & H.E. Robins has a high degree of infestation whatever the plot location. Euphorbia heterophylla L., Ageratum conyzoides L. and Panicum laxum Sw. show high levels of infestation in the plots out of the forest and start invading slowly the plots within the forest.